Vampire across the way - Sheldon, Dyan; Ross, Tony (Walker London, 2004)
A mysterious stranger has moved into the house over the road in the dead of night, and Benjy and Cas are convinced he's a vampire. All they have to do is prove it. But when they go to investigate, the boys get the shock of their lives